Sonification as a possible stroke rehabilitation strategy - Scholz, Daniel S.; Wu, Liming; Pirzer, Jonas; Schneider, Johann; Rollnik, Jens D.; Großbach, Michael; Altenmüller, Eckart O. (Frontiers in Neuroscience, 2014)
Despite cerebral stroke being one of the main causes of acquired impairments of motor skills worldwide, well-established therapies to improve motor functions are sparse. Recently, attempts have been made to improve gross motor rehabilitation by mapping patient movements to sound, termed sonification. Sonification provides additional sensory input, supplementing impaired proprioception. However, to date no established sonification-supported rehabilitation protocol strategy exists. In order to examine and validate the effectiveness of sonification in stroke rehabilitation, we developed a computer program, termed “SonicPointer”: Participants' computer mouse movements were sonified in real-time with complex tones. Tone characteristics were derived from an invisible parameter mapping, overlaid on the computer screen. The parameters were: tone pitch and tone brightness. One parameter varied along the x, the other along the y-axis. The order of parameter assignment to axes was balanced in two blocks between subjects so that each participant performed under both conditions. Subjects were naive to the overlaid parameter mapping and its change between blocks. In each trial a target tone was presented and subjects were instructed to indicate its origin with respect to the overlaid parameter mapping on the screen as quickly and accurately as possible with a mouse click. Twenty-six elderly healthy participants were tested. Required time and two-dimensional accuracy were recorded. Trial duration times and learning curves were derived. We hypothesized that subjects performed in one of the two parameter-to-axis–mapping better, indicating the most natural sonification. Generally, subjects' localizing performance was better on the pitch axis as compared to the brightness axis. Furthermore, the learning curves were steepest when pitch was mapped onto the vertical and brightness onto the horizontal axis. This seems to be the optimal constellation for this two-dimensional sonification.